Simulasi Monte Carlo Untuk Prediksi dan Analisis Tindak Pidana di Sumatera Utara - Gultom, Ledy Meva Tiurma; Felicia Eldora; Khoiriyati Azmi; Purba, Rut Omega; Karin Aulia Putri; Manullang, Sudianto; Nasution, Alvi Sahrin (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Crime data in North Sumatra Province obtained from the Central Statistics Agency shows an upward trend, peaking in 2023. This condition presents an urgent need for swift and appropriate policy intervention. The effectiveness of such policies is measured by their ability to significantly reduce crime rates. This study aims to forecast the trend of criminal acts in North Sumatra for the period 2024–2028 using the Monte Carlo Simulation method, based on historical data from 2000 to 2023. The stochastic simulation approach was chosen to accommodate the uncertainty and variability inherent in crime data. The results provide probabilistic predictions that can serve as a reference for the government in designing more adaptive and responsive crime prevention policies. This model is expected to offer realistic estimates of potential increases or decreases in crime, thereby enabling more targeted and data-driven decisions. Overall, the findings of this study contribute to the development of strategic, risk-based security policies that reflect the dynamic nature of criminal activity.